Clinical risk index of babies-II versus score for neonatal acute physiology-II in predicting mortality and morbidity in preterm babies - Madabhushi, Siddharth; Naik, Suhail A.; Shah, Mubashir H. (International Journal of Contemporary Pediatrics, 2022)
Background: The measurement of severity of illness using scoring systems is an important aspect in predicting mortality and morbidity in intensive care units which in turn can help in optimizing the limited healthcare resources in developing countries. The primary objective was to determine the correlation between clinical risk index of babies-II (CRIB-II) and score for neonatal acute physiology-II (SNAP-II) scores while the secondary objective was to identify which among them is superior in predicting mortality and morbidity in preterm neonates. Methods: The components of CRIB-II and SNAP-II scores were recorded prospectively over a period of 1 year in preterm very low birth weight (VLBW) babies and receiver-operating-characteristics (ROCs) were plotted for comparison. Correlation between CRIB-II and SNAP-II was examined by Pearson technique. The ability of CRIB-II and SNAP-II scores to correctly predict mortality, was assessed by calculating ROCs and their associated area under the curve (AUC). Results: Thirty nine neonates with a mean birth weight of 994.10 grams (SD±273.45 grams) and mean gestational age of 28.07 weeks (SD±2.29 weeks) were included in this study. The mean value of CRIB-II score and SNAP-II score was 8.54 (SD±4.67) and 9.82 (SD±8.93) respectively with a Pearson coefficient of 0.483 showing a modest correlation. CRIB-II (AUC 0.909) showed greater discrimination than SNAP-II (0.869) as a predictor of mortality. However, both the scores have poor discrimination when it comes to predicting neonatal morbidity. Conclusions: CRIB-II with its simplicity, need for uncomplicated variables and minimal time to generate a score for prediction of mortality and morbidity could be a useful tool in a busy neonatal intensive care unit (NICU).